26.8k views
0 votes
Find the first six terms of the sequence defined by each of these recurrence relations and initial conditions.

a) an=6an-1, a0=2
b) an=a2n-1, a1=2
c) an=an-1+3an-2, a0=1 , a1=2
d) an=nan-1+n2 an-2 a0=1 ,a1=1
e) an= an-1+an-3 , a0=1, a1=2 , a2=0

1 Answer

3 votes

Answer:

See explanation

Explanation:

Solving (a):


a_n = 6a_(n-1) where
a_0 = 2

n = 1


a_n = 6a_(n-1)


a_1 = 6a_(1-1)


a_1 = 6a_(0)

Substitute 2 for
a_0


a_1= 6 * 2


a_1= 12

n = 2


a_n = 6a_(n-1)


a_2 = 6a_(2-1)


a_2 = 6a_(1)

Substitute 12 for
a_1


a_2= 6 * 12


a_2= 72

n = 3


a_n = 6a_(n-1)


a_3 = 6a_(3-1)


a_3 = 6a_2

Substitute 72 for
a_2


a_3= 6 * 72


a_3= 432

n = 4


a_n = 6a_(n-1)


a_4 = 6a_(4-1)


a_4 = 6a_(3)

Substitute 432 for
a_3


a_4 = 6 * 432


a_4 = 2592

n = 5


a_n = 6a_(n-1)


a_5 = 6a_(5-1)


a_5 = 6a_4

Substitute 2592 for
a_4


a_5 = 6 * 2592


a_5 = 15552

n = 6


a_n = 6a_(n-1)


a_6 = 6a_(6-1)


a_6 = 6a_(5)

Substitute 15552 for
a_5


a_6 = 6 * 15552


a_6 = 93312


a_1= 12
a_2= 72
a_3= 432
a_4 = 2592
a_5 = 15552
a_6 = 93312

Solving (b):


a_n = a^2_{n - 1 where
a_1 = 2

We have


a_1 = 2 which serves as the first term

n =2


a_n = a^2_{n - 1


a_2 = a^2_(2-1)


a_2 = a^2_(1)

Substitute 2 for
a_1


a_2 = 2^2


a_2 = 4

n = 3


a_3 = a^2_(3-1)


a_3 = a^2_(2)


a_3 = 4^2


a_3 = 16

n = 4


a_4 = a^2_(4-1)


a_4 = a^2_3


a_4 = 16^2


a_4 = 256

n =5


a_5 = a^2_{5-1


a_5 = a^2_4


a_5 = 256^2


a_5 = 65536

n = 6


a_6 = a^2_{6-1


a_6 = a^2_{5


a_6 = 65536^2


a_6 = 4294967296


a_1 = 2
a_2 = 4
a_3 = 16
a_4 = 256
a_5 = 65536
a_6 = 4294967296

Solving (c):


a_n=a_(n-1)+3a_(n-2);
a_0=1 ; ;
a_1=2


a_1=2 ---- First term

n = 2


a_n=a_(n-1)+3a_(n-2); becomes


a_2=a_(2-1)+3a_(2-2)


a_2=a_1+3a_0

Substitute values for a1 and a0


a_2=2+3 * 1


a_2=2+3


a_2=5

n = 3


a_n=a_(n-1)+3a_(n-2); becomes


a_3=a_(3-1)+3a_(3-2)


a_3=a_(2)+3a_(1)


a_3=5+3 * 2


a_3=5+6


a_3=11

n = 4


a_n=a_(n-1)+3a_(n-2); becomes


a_4=a_(4-1)+3a_(4-2)


a_4=a_(3)+3a_(2)


a_4=11+3 * 5


a_4=11+15


a_4=26

n = 5


a_n=a_(n-1)+3a_(n-2); becomes


a_5=a_(5-1)+3a_(5-2);


a_5=a_(4)+3a_3


a_5=26+3 * 11


a_5=26+33


a_5=59

n = 6


a_n=a_(n-1)+3a_(n-2); becomes


a_6=a_(6-1)+3a_(6-2)


a_6=a_(5)+3a_4


a_6=59+3*26


a_6=59+78


a_6=137


a_1=2
a_2=5
a_3=11
a_4=26
a_5=59
a_6=137

Solving (d):


a_n=na_(n-1)+n^2a_(n-2);
a_0=1;
a_1=1


a_1=1 --- First term

n = 2


a_n=na_(n-1)+n^2a_(n-2) becomes


a_2=2 * a_(2-1)+2^2a_(2-2)


a_2=2 * a_1+4*a_0


a_2=2 * 1+4*1


a_2=2 +4


a_2=6

n = 3


a_n=na_(n-1)+n^2a_(n-2) becomes


a_3=3 * a_(3-1)+3^2 * a_(3-2)


a_3=3 * a_(2)+9 * a_(1)


a_3=3 * 6+9 * 1


a_3=18+9


a_3=27

n = 4


a_n=na_(n-1)+n^2a_(n-2) becomes


a_4=4*a_(4-1)+4^2*a_(4-2)


a_4=4*a_(3)+16*a_(2)


a_4=4*27+16*6


a_4=204

n = 5


a_n=na_(n-1)+n^2a_(n-2) becomes


a_5=5 * a_(5-1)+5^2 * a_(5-2)


a_5=5 * a_(4)+25 * a_(3)


a_5=5 * 204+25 *27


a_5=1695

n = 6


a_n=na_(n-1)+n^2a_(n-2) becomes


a_6=6 * a_(6-1)+6^2*a_(6-2)


a_6=6 * a_(5)+36*a_(4)


a_6=6 * 1695+36*204


a_6=17514


a_1=1
a_2=6
a_3=27
a_4=204
a_5=1695
a_6=17514

Solving (e):


a_n= a_(n-1)+a_(n-3);\ a_0=1; a_1=2; a_2=0

First term:
a_1=2

Second Term:
a_2=0

n = 3


a_n= a_(n-1)+a_(n-3) becomes


a_3= a_(3-1)+a_(3-3)


a_3= a_(2)+a_0


a_3= 0+1


a_3= 1

n = 4


a_n= a_(n-1)+a_(n-3) becomes


a_4= a_(4-1)+a_(4-3)


a_4= a_(3)+a_(1)


a_4= 1+2


a_4=3

n = 5


a_n= a_(n-1)+a_(n-3) becomes


a_5= a_(5-1)+a_(5-3)


a_5= a_(4)+a_(2)


a_5= 3 + 0


a_5= 3

n = 6


a_n= a_(n-1)+a_(n-3) becomes


a_6= a_(6-1)+a_(6-3)


a_6= a_(5)+a_(3)


a_6= 3 + 1


a_6= 4


a_1=2
a_2=0
a_3= 1
a_4=3
a_5= 3
a_6= 4

User Eisenhorn
by
4.5k points